2006
DOI: 10.1017/s0033291706007963
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of EMDR and trauma-focused cognitive-behavioral therapy in the treatment of PTSD: a meta-analytic study

Abstract: Our results suggest that in the treatment of PTSD, both therapy methods tend to be equally efficacious. We suggest that future research should not restrict its focus to the efficacy, effectiveness and efficiency of these therapy methods but should also attempt to establish which trauma patients are more likely to benefit from one method or the other. What remains unclear is the contribution of the eye movement component in EMDR to treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
222
2
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(255 citation statements)
references
References 34 publications
4
222
2
12
Order By: Relevance
“…EMDR is an evidence-based psychological treatment that is frequently used and effective in post-traumatic stress disorder (PTSD) and its affiliated symptoms (Bisson et al, 2007; Bradley, Greene, Russ, Dutra, & Westen, 2005; Seidler & Wagner, 2006). Desensitization and reprocessing of memories and images that contribute to the symptoms, such as events in which the tinnitus acquired negative meaning, may reduce tinnitus distress.…”
Section: Introductionmentioning
confidence: 99%
“…EMDR is an evidence-based psychological treatment that is frequently used and effective in post-traumatic stress disorder (PTSD) and its affiliated symptoms (Bisson et al, 2007; Bradley, Greene, Russ, Dutra, & Westen, 2005; Seidler & Wagner, 2006). Desensitization and reprocessing of memories and images that contribute to the symptoms, such as events in which the tinnitus acquired negative meaning, may reduce tinnitus distress.…”
Section: Introductionmentioning
confidence: 99%
“…In posttraumatic stress disorder (PTSD) there has been considerable research on whether CR adds any treatment effectiveness beyond prolonged trauma exposure. Several meta-analyses have concluded that individual trauma-focused CBT that includes exposure to an individual's memory of the trauma and its personal meaning is an effective treatment for PTSD (e.g., Bisson & Andrew, 2009;Seidler & Wagner, 2006; see also discussion by Ehlers et al, 2010). However, there is considerable controversy over whether CR of trauma-related thoughts and beliefs adds any therapeutic effectiveness over prolonged imaginal exposure to the trauma memory.…”
Section: Component Analysismentioning
confidence: 99%
“…Ambas consisten esencialmente en exposición sistemática, desensibilización y reestructuración cognitiva. En el caso de EMDR, se utilizan los movimientos oculares para facilitar este proceso, pero la utilidad de ello es controvertida 37,44,52 . La evidencia, por el contrario, indica que sería el componente conductual, común a todas las psicoterapias centradas en el trauma, el que explicaría su efecto benéfico 42 y no se han encontrado diferencias de efectividad entre la terapia cognitivo-conductual y EMDR en el tratamiento del TEPT 37 .…”
Section: Nivel IV Manejo Psiquiátrico Generalunclassified
“…En el caso de EMDR, se utilizan los movimientos oculares para facilitar este proceso, pero la utilidad de ello es controvertida 37,44,52 . La evidencia, por el contrario, indica que sería el componente conductual, común a todas las psicoterapias centradas en el trauma, el que explicaría su efecto benéfico 42 y no se han encontrado diferencias de efectividad entre la terapia cognitivo-conductual y EMDR en el tratamiento del TEPT 37 . Las psicoterapias sin un componente conductual, como las psicoterapias de apoyo, la hipnosis, la psicoterapia psicodiná-mica, etc, no han demostrado ser efectivas 31,34,40,63 ; sólo dos metaanálisis plantean lo contrario 29,46 .…”
Section: Nivel IV Manejo Psiquiátrico Generalunclassified